Usage of Silanes when Making Protective Coatings for Metal by Uv Curing - Aykasheva, O.S.; Babkin, O.E.; Babkina, L.A.; Proskuryakov, S.V.; Esenovsky, A.G. (Хімія, фізика та технологія поверхні, 2010)
Adhesive strength of coatings depends on the nature and density of adhesive bonds. It has been shown that using silanes with olefinic carbon as an adhesive layer on metal substrates lets increase significantly protective effectiveness and life time of UV lacquer coatings due to formation of the Me-О-Si-C covalent bonds. Silanes show optimum properties when unimolecular film is formed on the surface.